Mukhamandapa (front porch) of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The mukhamandapa (front porch) of the Mahakal Temple serves as a narrow corridor flanked by kaksahanas (seat backs) on either side, with four pillars supporting its flat roof. These pillars have square bases intricately carved with divine figures on all four sides. The upper section adopts an octagonal shape, embellished with miniature niches on all sides housing seated goddess figures. Crowning this, there's a band adorned with various figures and a kirtimukha (face of glory) motif.